2014
DOI: 10.4269/ajtmh.14-0127
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Seroprevalence and Risk Factors for Past and Recent Viral Transmission in Venezuela: A Comprehensive Community-Based Study

Abstract: Abstract. Dengue transmission in Venezuela has become perennial and a major public health problem. The increase in frequency and magnitude of recent epidemics prompted a comprehensive community-based cross-sectional study of 2,014 individuals in high-incidence neighborhoods of Maracay, Venezuela. We found a high seroprevalence (77.4%), with 10% of people experiencing recent infections. Multivariate logistic regression analysis showed that poverty-related socioeconomic factors (place and duration of residence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
69
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 48 publications
14
69
1
1
Order By: Relevance
“…The most common types of mosquito control measures employed by residents of Dhaka were use of bed nets, burning of mosquito coils and the use of insecticidal sprays. Consistent with other studies, we observed a significant association of both DENV seroprevalence and seroconversion with use of some personal mosquito control measures [11,5960]. In our evaluation of the effect of personal mosquito control measures on the risk of dengue infection, bed nets appeared to be associated with a lower likelihood of infection than the use of mosquito coils or insecticide sprays, which is consistent with findings reported by others [61].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The most common types of mosquito control measures employed by residents of Dhaka were use of bed nets, burning of mosquito coils and the use of insecticidal sprays. Consistent with other studies, we observed a significant association of both DENV seroprevalence and seroconversion with use of some personal mosquito control measures [11,5960]. In our evaluation of the effect of personal mosquito control measures on the risk of dengue infection, bed nets appeared to be associated with a lower likelihood of infection than the use of mosquito coils or insecticide sprays, which is consistent with findings reported by others [61].…”
Section: Discussionsupporting
confidence: 92%
“…In a study in southern Vietnam, Thai et al [56] found a positive association between some peri-domestic risk factors including discarded cans and pit latrines and a high prevalence of DENV antibodies. Similar to some of our findings, the pattern of DENV transmission occurring mainly (but not exclusively) at home was observed in studies conducted in Singapore [40], Brazil [41] and Venezuela [11]. Braga et al [39] observed that household members who spent more time within homes, such as domestic workers and housewives, were at a higher risk of acquiring recent dengue infection.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…High and age-specific DENV IgG seroprevalence is consistent with long-term endemic circulation of DENV [27], and it is in accordance with a recent community-based survey carried out in the Santa Cruz district of Medellin [26] after the 2010 outbreak. Similar results in younger population have been reported in countries like Nicaragua [10, 28], Dominican Republic [29], Southern Vietnam [14], and Venezuela [30]. …”
Section: Discussionsupporting
confidence: 86%
“…Those findings evidence that, through 2010, the combination of poorly and crowded socioeconomic living conditions and densest human and mosquito populations was associated with a higher DENV transmission risk. As reported by other authors, those factors are determinants for the permanent DENV transmission [30]. The House Index (HI), Container Index (CI), and Breteau Index (BI) are recommended by PAHO (Pan American Health Organization) for monitoring vector abundance and targeting and evaluating vector control interventions.…”
Section: Discussionmentioning
confidence: 99%